Association between lymphocytotropic virus type I (HTLV-I) infection and Pacific spastic paraparesis (Colombia Medica, 1986)
The information related to paraparesia del Pacífico (PEP) and tropical spastic paraparesis (TSP) from Jamaica, Martinique, and Japan, it was considered that the HTVL-I virus could be the causal agent of the disease.The epidemiology and some recent information on the HTVL-I virus were reviewed. The results of a study of cases and controls performed in Tumaco (Pacific Coast of Colombia) indicate a causal relationship between PEP and HTVL-I virus. Some therapeutical considerations were given. The name mieloneuroaptía associated con retrovirus (MAR) is proposed for this clinical entity of worldwide distribution.